Learning from COVID-19 for Mitigating the Next Possible Pandemic: Nutrition, Lifestyle, Risk Factors and Non-Pharmaceutical Interventions - Ramzan, Saniya; Saeed, Maryam; Ali, Zain; Tariq, Muhammad Rizwan (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
The COVID-19 pandemic has sparked a paradigm change in pandemic preparedness measures, motivating an investigation of non-pharmaceutical therapies. This research dives into the lessons learned from COVID-19 to strengthen our strategy to prevent future pandemics. The study aimed to extract valuable insights from the COVID-19 experience, extrapolating lessons learned to develop strong strategies that include diet, lifestyle, risk factors and non-pharmaceutical treatments. Nutrition and lifestyle influences on illness susceptibility were studied using a comprehensive examination of scholarly literature, reports and epidemiological studies. Role of essential risk variables was investigated in magnifying pandemic outcomes and the efficiency of non-pharmaceutical treatments in reducing infectious agent transmission. The analysis demonstrates the long-term utility of COVID-19 findings. This review emphasizes the importance of nutrition and lifestyle variables in determining susceptibility to infectious illnesses. Furthermore, a detailed examination of risk variables shows critical predictors of pandemic severity. Most significantly, the findings highlight the effectiveness of non-pharmaceutical measures, emphasizing their vital role in pandemic containment. This study has far-reaching ramifications that advocate for a paradigm change towards comprehensive pandemic preparation using the lessons learned during COVID-19. Research findings highlight the need for a multifaceted strategy, including diet, lifestyle changes, targeted risk reduction and non-pharmaceutical therapies. This study provides a road map for improving global resilience to potential future pandemics, calling for preventative strategies beyond pharmacological remedies.